POTENSI EKOSISTEM PADANG LAMUN DI KAWASAN WISATA BAHARI GUGUSAN PULAU PARI, DKI JAKARTA - Aditano Yani Retawimbi (Sekolah Tinggi Pariwisata Ambarrukmo Yogyakarta, 2018)
Marine Tourism Area at Pari Island cluster has a variety of ecosystems, one of them is the seagrass ecosystem. Seagrass is one of the coastal and marine resources, which has the potential to be developed as a resource for tourist attraction in the marine tourism area of Pari Islands. Purpose this study is to describe seagrass conditions, is it worthed to be used as a tourist attraction by conducting field research of species composition, distribution, percent cover at marine tourism territory Pari Islands, DKI Jakarta. The study was conducted from April-May 2017 with the descriptive method, where this method is done by describing or describe seagrass conditions. Survey and field data acquisition carried out in Pari Islands at 10 stations using the quadrant transect method. Based on field observation, in the field was found 5 species of seagrass species Cymodocea rotundata, Enhalus acoroides, Halophila ovalis, Syringodium isoetifolium and Thalassia hemprichii that can be a potential attraction for marine tourism. The results of calculations percent cover of seagrass shows that the highest percent cover was at station 9 with total percent was 76,2 %, while the lowest percent cover was at station 2, amounting to 20,4 %.Keywords: Marine Tourism, Pari Islands, Seagrass Beds